2009
DOI: 10.3748/wjg.15.106
|View full text |Cite
|
Sign up to set email alerts
|

Iron homeostasis and H63D mutations in alcoholics with and without liver disease

Abstract: AIM:To evaluate the prevalence of HFE gene mutation and indices of disturbed iron homeostasis in alcoholics with and without liver disease. METHODS:One hundred and fifty-three heavy drinkers (defined as alcohol consumption > 80 g/d for at least 5 years) were included in the study. These comprised 78 patients with liver disease [liver disease alcoholics (LDA)] in whom the presence of liver disease was confirmed by liver biopsy or clinical evidence of hepatic decompensation, and 75 subjects with no evidence of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…Genotype may contribute to iron overload with variable penetrance and phenotypic expression may be influenced by cofactors (8,(28)(29)(30) and other additive individual factors (1,5,28). It is therefore reasonable to observe a lack of significance in the correlation between iron blood indicators and body stores, such as skin and liver over a long time-period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Genotype may contribute to iron overload with variable penetrance and phenotypic expression may be influenced by cofactors (8,(28)(29)(30) and other additive individual factors (1,5,28). It is therefore reasonable to observe a lack of significance in the correlation between iron blood indicators and body stores, such as skin and liver over a long time-period.…”
Section: Discussionmentioning
confidence: 96%
“…It is therefore reasonable to observe a lack of significance in the correlation between iron blood indicators and body stores, such as skin and liver over a long time-period. This raises the possibility that, in some cases, there is a differential cellular iron handling, which results in variable accumulation of iron (5,6,8,15,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 97%
“…Simple steatosis is usually considered benign, but the development of NASH is recognized as a precursor of more severe liver disease, and in some cases, cirrhosis and hepatocellular carcinoma (Machado et al, 2009). Machado et al, (2009) reported that pathogenesis of NASH can be explained by the "two-hit" hypothesis, (a) insulin resistance and the resultant steatosis being the "first hit". Hyperinsulinemia, increased peripheral lipolysis and reduced -oxidation lead to fat accumulation (b) the "second hit"-increased ROS/RNS.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Moreover, serum ferritin levels are higher in ALD patients than in non-alcoholic patients with other chronic liver diseases, such as autoimmune disorders or chronic hepatitis C virus (HCV) infection. Interestingly, upon alcohol withdrawal, the increased serum ferritin levels have been shown to rapidly decrease (2,24) . Alcohol consumption has been implicated as the main cause of increased serum ferritin levels in the general population (17,24) .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, upon alcohol withdrawal, the increased serum ferritin levels have been shown to rapidly decrease (2,24) . Alcohol consumption has been implicated as the main cause of increased serum ferritin levels in the general population (17,24) . The apparent sensitivity of this pathological process was further indicated by a study showing that even moderate alcohol ingestion can affect iron metabolism (18) .…”
Section: Introductionmentioning
confidence: 99%